Peripheral Leukocytosis Is Inversely Correlated with Intratumoral CD8+ T-Cell Infiltration and Associated with Worse Outcome after Chemoradiotherapy in Anal Cancer - Martin, Daniel; Rödel, Franz; Winkelmann, Ria; Balermpas, Panagiotis; Rödel, Claus; Fokas, Emmanouil (Frontiers in Immunology, 2017)
Peripheral blood leukocytosis has been implicated in promoting tumor progression leading to worse survival but the mechanisms behind this phenomenon remain unexplored. Here, we examined the prognostic role of pretreatment white blood cell (WBC) count and clinicopathologic parameters in the context of CD8+ tumor-infiltrating-lymphocytes (TIL) and MPO+ tumor-associated neutrophils (TAN) in patients with anal squamous cell carcinoma (ASCC) treated with definitive chemoradiotherapy (CRT). After a median follow-up of 26 months, leukocytosis correlated with advanced T-stage (p < 0.001) and N-stage (p < 0.001), and predicted for worse distant-metastasis-free survival (DMFS, p = 0.006), disease-free-survival (DFS, p = 0.029) and overall survival (OS, p = 0.013). Importantly, leukocytosis was associated with a lower intraepithelial CD8+ TIL density (p = 0.014), whereas low CD8+ TIL expression in the intraepithelial compartment was associated with worse DFS (p = 0.028). Additionally, high TAN expression in the peritumoral compartment was associated with a significantly lower density of CD8+ TIL (p = 0.039), albeit TAN expression lacked prognostic value. In conclusion, leukocytosis constitutes an important prognostic marker in ASCC patients treated with chemoradiotherapy. In conjunction with intratumoral TIL and TAN, these data provide for the first time important insight on the correlation of peripheral blood leukocytosis with the intatumoral immune contexture, and could be relevant for future patient stratification using immunotherapies in ASCC.